Functional Disconnection of the Angular Gyrus Related to Cognitive Impairment in Patients With Type 2 Diabetes Mellitus - Qi, Fei; Zhang, Dongsheng; Gao, Jie; Tang, Min; Wang, Man; Su, Yu; Lei, Yumeng; Shao, Zhirong; Zhang, Xiaoling (Frontiers in Human Neuroscience, 2021)
Type 2 diabetes mellitus (T2DM) is related to a variety of cognitive impairments that may even progress to dementia. Studies have found the angular gyrus (AG) is a cross-modal integration hub that is involved in a variety of cognitive processes. However, few studies have focused on the patterns of resting-state functional connections (rsFCs) of the AG in patients with T2DM. This study explored the FC between the AG and the whole brain and the relationship between the FC and clinical/cognitive variables in patients with T2DM. Forty-four patients with T2DM and 43 sex-, age-, and education-matched healthy controls (HCs) underwent resting-state fMRI and received neuropsychological assessments. Compared with the control group, the T2DM group showed abnormal rsFCs between the AG and multiple brain regions. The FC between the left AG and the left medial temporal lobe in the T2DM group was positively correlated with scores on the Montreal Cognitive Assessment, after a Bonferroni correction (r = 0.40, P = 0.009). Collectively, patients with T2DM have abnormal FCs between the AG and extensive brain regions that may be related to various cognitive processes.